Fever pitch [videorecording (DVD)]. - Barrymore, Drew; Fallon, Jimmy (20th Century Fox, 2005)
According to Red Sox super-fan Ben Wrightman, finding romance is about as likely as his beloved team winning the World Series. But when Ben scores a beautiful new girlfriend, suddenly anything is possible.